THE DIFFERENCE OF BREAST MILK PRODUCTION IN POST PARTUM MOTHERS PERFORMED ACUPRESSURE POINTS TECHNIQUE FOR LACTATION AND BREAST CARE TECHNIQUE - Hamimatus Zainiyah (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 1970)
During pregnancy, the prolactin hormone from placenta increases but breast milkusually does has come out because it is still inhibited by high estrogen levels. On the secondor third day of postpartum, estrogen and progesterone levels drop significantly, so the effectof prolactin is more dominant and secretion of breast milk begins. By breastfeeding earlierthe secretion of breast milk gets smoother. Based on a preliminary study, 46.0% of postpartum mothers experienced non-breast milk. This study aims to determine the differences inthe production of breast milk in post partum mothers who performed acupressure techniquesfor lactation and breast care techniques.This research is a kind of research of quasy exsperimental design with non equivalentcontrol group design. The samples were 7 post partum mothers that used acupressuretechniques for lactation and 7 post partum mothers used breast care techniques from inFebruary to March 2017. The sampling technique used was non probability sampling(consecutive sampling).From the statistic test of Independent T-Test indicates that α = 0.05 and P value 0.03 thusP Value<alpha (0.03 <0.05) so that H0 is rejected and Ha accepted there was a difference inbreast milk production in post partum mothers performed acupressure and breast caretechniques in the BPM Sri Wahyuni area, S.ST Surabaya. Midwives are able to socialize this acupressure technique to all post partum mothers, sothat midwives can help secretion of breast milk production for post partum mothers withacupressure techniques with relatively cheaper costs.